Antimicrobial, Antioxidant, Anti-Inflammatory Activities of Eight Essential Oils Obtained from Traditional Chinese Medicines Using Supercritical Fluid Extraction Coupled Molecular Distillation. Issue 5 (3rd September 2022) - Zhong, Jialun; Muhammad, Nadeem; Yang, Xiaoying; Li, Jiasheng
Abstract: Atractylodes chinensis (DC.) Koidz., Magnolia officinalis Rehd. et Wils., Citrus reticulata Blanco, Amomum villosum Lour., Pogostemon cablin (Blanco) Benth., Mosla chinensis Maxim., Zingiber officinale Rosc., and Artemisia argyi Lévl. et Vant are eight of the extensively used herbs among Traditional Chinese Medicines (TCM) with a long history. The essential oil (EO) extracts of the eight TCMs were obtained using supercritical fluid extraction coupled with molecular distillation to investigate the chemical composition, antimicrobial, antioxidant activities, and anti-inflammatory activity for further exploration of the underlying mechanism of the various biological activities. The chemical components of the EO were analyzed by GC-MS. The antimicrobial activity was evaluated by the agar-well diffusion assay and the minimum inhibitory concentration assay. The antioxidant activity of the EO was evaluated by 1, 1-diphenyl-2-picrylhydrazyl radical and 2, 2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid ammonium salt assays. The anti-inflammatory activity of a recipe named "Shenshusan" was evaluated by the xylene-induce ear vasodilatation assay and the acetic acid-induce capillary permeability enhancement assay. Chemical constituents of the EO varied markedly among the eight species of TCMs. The EOs from Mosla chinensis and Artemisia argyi exhibited strong antimicrobial activity while the EOs from Magnolia officinalis, Mosla chinensis and Zingiber officinale exhibited strong antioxidant activity. The recipe "Shenshusan" showed significant anti-inflammatory activity (340 mg/kg for mice). This study contributes to what is known about the eight kinds of TCM possesses the potent antimicrobial, antioxidant, and anti-inflammatory activity which held great potential and can help guide future recommendations and interventions for food, medicine, and cosmetics application.